2000
DOI: 10.1046/j.1472-765x.2000.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a campylobacter-free pig population through a top-down approach

Abstract: A S . 2000. Fattening pigs are often infected with campylobacter. To eliminate campylobacter from the pig population, a topdown approach, involving the breeding and reproduction farms, seems appropriate. In order to investigate the effectiveness of a top-down approach, sows' faeces from the following farms were analysed for the presence of campylobacter: one speci®c pathogen free (SPF) farm, three top-breeding farms with no connection with SPF breeding, and a breeding farm repopulated with SPF sows after a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…As reported for Campylobacter coli in pigs (38,49,50), some Arcobacter strains spread over the pig house, resulting in dominant strains in several animals. For example strains B1, B4, B8, and B11 were predominantly excreted by several pigs throughout the finishing period on farm D. The dominance of such strains may suggest a greater capacity to survive the environmental stresses and to colonize the host gut, as previously described for Campylobacter jejuni (12,33).…”
Section: Discussionmentioning
confidence: 67%
“…As reported for Campylobacter coli in pigs (38,49,50), some Arcobacter strains spread over the pig house, resulting in dominant strains in several animals. For example strains B1, B4, B8, and B11 were predominantly excreted by several pigs throughout the finishing period on farm D. The dominance of such strains may suggest a greater capacity to survive the environmental stresses and to colonize the host gut, as previously described for Campylobacter jejuni (12,33).…”
Section: Discussionmentioning
confidence: 67%
“…Weijtens et al (2000) reported that 22-98% of fecal samples from fattening pigs in the Netherlands were positive for Campylobacter. A similar study from the USA reported that 70-100% of pigs at slaughter (depending on the farm and the date samples were collected) were positive for Campylobacter (Harvey et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The apparent high exposure from the paddock environment implies that Campylobacter spp. infections in organic pigs might be more persistent, not least due to the difficulties in cleaning of the outdoor paddocks and practicing good hygiene, which is important to reduce infections Weijtens et al, 2000).…”
Section: Discussionmentioning
confidence: 99%